The Effect of Ratio Seaweed (Eucheuma cottonii) And Strawberry (Fragaria xananassa) On The Characteristics of Jam - Ariestini, Ni Putu; Suter, I Ketut; Timur Ina, Putu (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 5 No 2 (2018): Scientific Journal of Food Technology (September), 2018)
This study aimed to determine the effect of ratio seaweed and strawberry on the characteristics of jam and to find out the ratio of seaweed and strawberry to produce jam with the best characteristics. This study used Completely Randomized Design for physical and chemical characteristics while sensory evaluation was analyzed using Randomized Block Design using seawed and strawberry treatment ratio which consist of 6 levels such as: 100% seaweed : 0% strawberry, 90% seaweed : 10% strawberry, 80% seaweed : 20% strawberry, 70 % Seaweed : 30% strawberry, 60% seaweed : 40% strawberry, and 50% seaweed : 50% strawberry with 3 replications to obtain 18 units of experiment. The results showed that the ratio of seaweed and stra+wberry had a significant effect on total soluble solids, acidity, moisture content, viscosity, vitamin C, anthocyanin, color, aroma, taste, texture (score and hedonic), overall acceptance and smear (hedonic). Treatment ratio of 50% seaweed with 50% strawberry yield best characteristic with total dissolved solids 61,33 0Brix, acidity 3.18, water content 26,9%, viscosity 24,00 cps, vitamin C 13,49 mg / 100g,  total anthocyanin 7,02 mg / 100g, red color and like, typical aroma of strawberry and very like, slightly sweet taste and like, soft texture and like, overall acceptance of like, smear of like